Results of the assessment of the motor vehicle user's charge utilization in the Philippines - Napalang, Sheilah G. (PIDS Research Paper Series, 2018)
Road funds like the Motor Vehicle User's Charge (MVUC) fund in the Philippines are earmarked funds that ensure a stable flow of resources, particularly for public road development projects. However, shortcomings from project identification to fund disbursement hamper effective implementation of the MVUC funding scheme. In assessing the different MVUC process, this paper finds that transparency and efficiency in collection should be improved through automation and accurate recording. Project identification and investment programming must also adhere to the recommended procedures in the operating manual. As the study finds indications of fund underutilization, it suggests accelerating fund utilization through advance project development and investment programming. Looking at five MVUC-funded projects, it observes that only one of the five projects had an impact monitoring system. Nevertheless, findings from field visits and interviews with beneficiaries reveal that there are positive benefits from the MVUC mechanism. A closer look at successful cases in other countries also reveals good practices that are worth noting.